Dramatografia - Krajewska, Anna (Przestrzenie Teorii, 2017)
The article presents the concept of dramatography as being created by “writing drama”. The author treats drama as a fluid concept, historically variable, non-binary compared to theatre, establishing performative relations interwoven with other arts. Dramatography is a response to limitations resulting from the use of the concepts of adaptation, interpretation and intersemiotic translation in the former binary system in drama and theatre. Referring to Hans Ulrich Gumbrecht’s concept of “producing presence”, the author shows the role of manifesting oneself as a counterweight to meaning in the process through which dramatography emerges.